PENERAPAN MODEL PEMBELAJARAN CROSSWORD PUZZLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM PELAJARAN SEJARAH KELAS XII TKR SMK NEGERI 5 PEKANBARU - Nurul Aisyah Febriani; Bedriati Ibrahim; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the low student learning outcomes in class XII history subjects at SMK 5 Pekanbaru. Based on these problems, the formulation of the problem in this study is whether the application of the crossword puzzle learning model can improve the learning outcomes of students of class XII TKR Smk Negeri 5 Pekanbaru. The purpose of this study was to determine the activities of teachers and students in the implementation of the learning process using the crossword puzzle model and to determine the effect of this learning model on the learning outcomes of students of class XII TKR Smk Negeri 5 Pekanbaru on historical subjects. This research was conducted in two cycles, in the first cycle the learning outcomes of students achieved classical completeness of 52.38% and increased in the second cycle reaching 90.48%. Based on the results of these studies it can be concluded that the application of the crossword puzzle learning model can improve student learning outcomes in the class XII history lesson of SMK Negeri 5 Pekanbaru.Key Words: Crossword Puzzle Model, Learning Outcomes